The Concept of Love in Hasrat Mohani’s Poetry - Haider, Sajjad (Zaban-o-Adab, 2025)
In the poetry of Hasrat Mohani, there is also a beautiful combination of ishq e majazi and ishq e haqiqi. In his poetry, love emerges as a pure and selfless emotion. He has presented the affairs of love and affection in his poetry in very simple and easy words. As well as the simplicity and eloquence of the language, sincerity and truthfulness are also seen in his poetry. To him, love is not just the name of an emotional state but a true and eternal experience. In his poetry, he describes the feelings of love and affection in a unique way which differs his poetry from traditional love poetry. For him, love is a true, pure and eternal experience in which not only the adoration of the beloved but also a deep expression of the insensibility, helplessness and departing of a true lover is seen